2016
DOI: 10.9744/dimensi.43.2.85-92
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Approach of Sustainability in Dwellings Culture Riparian Community Musi River Palembang

Abstract: Dwelling Riparian is not an archaeological artifacts or ruins of civilization, but the physical figure of communities that are still alive and live. Socially, the Musi River not merely as a means of transport and make a living alone. Moreover Musi River Palembang form of existence of cultural sovereignty. Riverside settlements are not only inherent elegance spatial pattern alone, but also contains exemplary values, philosophy, and belief in the primordial Palembang riverside cultural background and meaning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(1 reference statement)
0
5
0
1
Order By: Relevance
“…Research about dwelling of a certain group of people in Indonesia is still very interesting to continue to do cause of the unique of its local values. There is a research which revealed evolution processes of dwelling culture and to compare the traditional spatial forms and the transformed ones, and also to emphasize the former attitude and to propose a sustainable strategy for developing the dwelling type by respecting and adopting the traditional culture and historic apologue (Wicaksono et al, 2016). In the other case, the phenomenon of a dwelling should be a manifestation of the dynamic roles of male and female members of the house and the circular arrangement of the space around the fireplace at the centre of the house follows the dynamic of gender duality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research about dwelling of a certain group of people in Indonesia is still very interesting to continue to do cause of the unique of its local values. There is a research which revealed evolution processes of dwelling culture and to compare the traditional spatial forms and the transformed ones, and also to emphasize the former attitude and to propose a sustainable strategy for developing the dwelling type by respecting and adopting the traditional culture and historic apologue (Wicaksono et al, 2016). In the other case, the phenomenon of a dwelling should be a manifestation of the dynamic roles of male and female members of the house and the circular arrangement of the space around the fireplace at the centre of the house follows the dynamic of gender duality.…”
Section: Introductionmentioning
confidence: 99%
“…In the other case, the phenomenon of a dwelling should be a manifestation of the dynamic roles of male and female members of the house and the circular arrangement of the space around the fireplace at the centre of the house follows the dynamic of gender duality. Its fact shows that the phenomenon of a dwelling was unique and full of different values (Nurdiah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it needs to be refined, generalized, and redesigned [77]. In order to respond to different external impacts, we need to combine diverse cultures, change our living habits, modernize according to climatic factors, and re-create them according to modern pattern design principles [78].…”
Section: Proposals: Artistic Element Extraction and Application Methodsmentioning
confidence: 99%
“…This change cannot be separated from the process of meaning by the community, along with the socio-cultural processes that occur. The dynamics of cultural identity then affect changes in the form and layout of the house (Bambang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%